High-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy and preparation method and application thereof
Through the design and hot-rolling deformation treatment of high-strength and high-plastic Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy, the problems of low strength and insufficient ductility during high-speed rotation of traditional soft magnetic materials are solved, and the problem of low strength and insufficient ductility during high-speed rotation is realized. Excellent mechanical and soft magnetic properties, suitable for high-speed motors and other fields.
Patent Information
- Application Number
- CN202411420101.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-10
AI Technical Summary
Traditional soft magnetic materials have low strength during high-speed rotation, lack ductility, and are difficult to meet the use under extreme load conditions. The strengthening mechanism leads to hindering the movement of the magnetic domain wall, deteriorating the soft magnetic performance.
High-strength, high-plastic Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy is used to improve the room temperature tensile strength and fracture toughness of the material through specific element ratios and hot-rolling deformation treatment, while maintaining excellent soft magnetic properties. .
It has achieved a small magnetic material with high saturation magnetization and coercivity, and has high room temperature tensile yield strength, tensile strength and elongation after break, and is suitable for high-speed motors and other fields.
Smart Images

Figure CN119287240A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to high entropy alloy technology, and in particular to a high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high entropy alloy, a preparation method and application thereof. Background Art
[0002] The rotor core of a high-speed motor requires soft magnetic materials that not only have excellent soft magnetic properties to achieve efficient conversion of electromagnetic energy and mechanical energy, but also require high strength to resist the huge centrifugal force generated by the rotor core during high-speed rotation. At the same time, good plasticity is also the key to ensure the safe operation of high-speed motors. However, the strengthening mechanisms used in traditional structural materials (such as fine grain strengthening, precipitation strengthening, and dislocation strengthening, etc.) will cause long-range stress in the material, which will hinder the movement of the magnetic domain wall and seriously deteriorate the soft magnetic properties of the material. Therefore, the existing commercial soft magnetic alloys such as FeSi alloys, FeCo alloys, and FeNi alloys have low strength, and soft magnetic materials such as amorphous and ferrites lack ductility. These materials are difficult to meet the use under extreme load conditions. Therefore, it is urgent to solve the contradiction between mechanical properties and soft magnetic properties and design soft magnetic materials with excellent mechanical properties. Summary of the invention
[0003] The purpose of the present invention is to propose a high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high entropy alloy to solve the problems of low strength of traditional structural materials and lack of ductility of soft magnetic materials such as amorphous and ferrite. The high entropy alloy has excellent soft magnetic properties and exhibits excellent room temperature tensile strength and fracture toughness. The high concentration of Fe, Co and Ni elements in the alloy of the present invention enables the alloy to have high saturation magnetization, and the addition of Al, Ti and Mo elements can significantly improve the strength of the alloy.
[0004] It should be noted that, in the present invention, unless otherwise specified, the specific meaning of "including" in relation to composition limitations and descriptions includes both open-ended "including", "comprising", etc. and similar meanings, as well as closed-ended "composed of", "composed of", etc. and similar meanings.
[0005] To achieve the above object, the technical solution adopted by the present invention is: a high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy, the general formula of which is Fe a Co b Ni c Al d Ti e Mo f, where 25%≤a≤40%, 28%≤b≤45%, 20%≤c≤30%, 3%≤d≤9%, 2%≤e≤8%, 0.1%≤f≤0.5%, and a+b+c+d+e+f=100%, a, b, c, d, e and f are the molar percentages of the corresponding elements respectively.
[0006] Furthermore, the general formula Fe a Co b Ni c Al d Ti e Mo f Satisfies: 60%≤a+b≤70%, 6%≤d+e≤15%.
[0007] Furthermore, the high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy, whose general formula is Fe a Co b Ni c Al d Ti e Mo f , among which 29.5%≤a≤38.2%, 29%≤b≤40.5%, 18.5%≤c≤26%, 3.5%≤d≤9.2%, 2.5%≤e≤8.2% and 0.1%≤f≤0.5%.
[0008] Furthermore, the high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy has a tensile yield strength of 800MPa to 1300MPa, a tensile strength of 1100MPa to 1700MPa, and an elongation after fracture of 10% to 40%.
[0009] Furthermore, the saturation magnetization intensity (Ms) of the high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy is 115emu / g to 140emu / g, and the coercive force (Hc) is 0.5Oe to 4Oe.
[0010] Another object of the present invention is to disclose a method for preparing a high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy, comprising the following steps:
[0011] Step 1, weigh the raw materials according to the molar ratio of each component in the general formula: Fe, Co, Ni, Al, Ti and Mo;
[0012] Step 2: placing the raw materials into a vacuum arc melting furnace and melting them under argon protection to obtain a Fe-Co-Ni-Al-Ti-Mo high entropy alloy ingot;
[0013] Step 3: The Fe-Co-Ni-Al-Ti-Mo high entropy alloy ingot is subjected to hot rolling deformation treatment, and the hot-rolled alloy is kept at 1100° C. to 1250° C. for 10 to 30 minutes to prepare a Fe-Co-Ni-Al-Ti-B high-strength plastic soft magnetic high entropy alloy.
[0014] Furthermore, the purity of Fe, Co, Ni, Al, Ti and Mo is all above 99.5wt.%.
[0015] Furthermore, before melting the alloy raw materials, the low melting point Al is placed at the bottom of the crucible, the high melting point Mo and Ti elements are placed at the top, and the remaining Fe, Co, and Ni elements are placed in the middle. That is, Al, Fe, Co, Ni, Ti, and Mo raw materials are placed in the vacuum arc melting furnace in sequence.
[0016] Furthermore, before smelting, the vacuum in the arc furnace smelting chamber should be pumped to 3×10 -3 ~4×10 -3 Pa, and then high-purity argon gas is filled in to -0.05~-0.04MPa.
[0017] Furthermore, before smelting the alloy, the single-substance Ti ingot needs to be repeatedly smelted 3 to 5 times, each time for 1 to 3 minutes, so that it can fully react with the remaining oxygen in the smelting chamber.
[0018] Further, the current for melting the alloy is 300-550A, and the melting is repeated 5-8 times, each time for 1-4 minutes. Preferably, the current for melting the alloy is 350-520A, and the melting is repeated 5-7 times, each time for 2-3 minutes.
[0019] Furthermore, the rolling temperature of the hot rolling deformation treatment is 900-1200° C., and the total deformation amount is 60%-90%.
[0020] Furthermore, the Fe-Co-Ni-Al-Ti-Mo high entropy alloy ingot is kept at the rolling temperature for 10 to 60 minutes, hot rolled and deformed, and then air-cooled. The subsequent heat treatments are all water-cooled.
[0021] Another object of the present invention is to disclose a high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy for use in the electromagnetic field.
[0022] Furthermore, the high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy is particularly suitable for metal parts of motors, generators and solenoid valves.
[0023] Furthermore, the high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy is particularly suitable for metal parts in high-speed motors, solenoid valves and transformers.
[0024] The high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy of the present invention has a scientific and reasonable formula, a simple and easy preparation method, and has the following advantages compared with the prior art:
[0025] 1) The high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy of the present invention includes specific element selection and reasonable ratio. High concentrations of ferromagnetic elements Fe, Co and Ni can improve the saturation magnetization intensity of the alloy, and Al, Ti and Mo elements can improve the strength of the material.
[0026] 2) The high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy of the present invention exhibits excellent room-temperature tensile properties after high-temperature hot rolling and heat treatment, with a tensile yield strength of up to 1046MPa, a tensile strength of up to 1230Mpa, and an elongation after fracture exceeding 21%.
[0027] 3) The high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy of the present invention has excellent soft magnetic properties, with a saturation magnetization (Ms) exceeding 120.8emu / g and a coercive force (Hc) less than 1.26Oe.
[0028] 4) The raw materials of the high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy of the present invention are easy to obtain, the preparation process is simple and easy, and the excellent comprehensive performance makes the alloy have broad application prospects in the soft magnetic field under extreme load conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The Fe prepared in Example 1 of the present invention 34.9 Co 29 Ni 25 Al6Ti5Mo 0.1 Room temperature tensile curves of soft magnetic high entropy alloys;
[0030] Figure 2 The Fe prepared in Example 1 of the present invention 34.9 Co 29 Ni 25 Al6Ti5Mo 0.1 Magnetic hysteresis loop of soft magnetic high entropy alloy (left) and local magnification of the central area (right);
[0031] Figure 3 The Fe prepared in Example 1 of the present invention 34.9 Co 29 Ni 25 Al6Ti5Mo 0.1 XRD diffraction analysis pattern of soft magnetic high entropy alloy;
[0032] Figure 4 The Fe prepared in Example 1 of the present invention 34.9 Co 29 Ni 25 Al6Ti5Mo 0.1 SEM microstructure of soft magnetic high entropy alloy;
[0033] Figure 5 The Fe prepared in Example 2 of the present invention 31.8 Co 32 Ni 25 Al6Ti5Mo 0.2 Room temperature tensile curves of soft magnetic high entropy alloys;
[0034] Figure 6 The Fe prepared in Example 2 of the present invention 31.8 Co 32 Ni 25 Al6Ti5Mo 0.2 Magnetic hysteresis loop of soft magnetic high entropy alloy (left) and local magnification of the central area (right);
[0035] Figure 7 The Fe prepared in Example 2 of the present invention 31.8 Co 32 Ni 25 Al6Ti5Mo 0.2 XRD diffraction analysis pattern of soft magnetic high entropy alloy.
[0036] Figure 8 The Fe prepared in Example 2 of the present invention 31.8 Co 32 Ni 25 Al6Ti5Mo 0.2 SEM microstructure of soft magnetic high entropy alloy.
[0037] Fig. 9 It is a comparison chart of the tensile yield strength of the soft magnetic high entropy alloys in Examples 1 and 2 of the present invention and commercial soft magnetic alloys. DETAILED DESCRIPTION
[0038] The present invention is further described below with reference to the examples. The description of the technical features described below is based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples. It should be noted that:
[0039] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.
[0040] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints A and B.
[0041] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.
[0042] In this specification, the word "may" means both performing a certain process and not performing a certain process.
[0043] In this specification, the use of "optional" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.
[0044] In this specification, when "normal temperature" or "room temperature" is used, the temperature may be 15-25°C.
[0045] In this manual, the reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.
[0046] Example 1
[0047] This embodiment discloses a high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy, the general formula of which is Fe 34.9 Co 29 Ni 25 Al6Ti5Mo 0.1 .
[0048] In this embodiment, the preparation method of the high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy is as follows:
[0049] Step 1: Weigh pure raw materials with a purity of more than 99 wt.% such as Fe, Co, Ni, Al, Ti and Mo according to the general formula.
[0050] Step 2: Place the raw materials in a non-consumable vacuum arc melting furnace, with Al at the bottom, Ti and Mo at the top, and the rest in the middle. Close the melting chamber and evacuate to 4×10 -3 Pa, then fill with high-purity argon to -0.05MPa, melt the Ti ingot for 80s, turn the titanium ingot over, repeat the above operation 3 times, remove the remaining oxygen in the furnace, and then melt Fe 34.9 Co 29 Ni 25 Al6Ti5Mo 0.1 High entropy alloy, the current is controlled at 500A for 2 minutes, the sample is turned over, and the above operation is repeated to obtain Fe 34.9 Co 29 Ni 25 Al6Ti5Mo 0.1Soft magnetic high entropy alloy ingot.
[0051] Step 3: Fe obtained in step 2 34.9 Co 29 Ni 25 Al6Ti5Mo 0.1 The soft magnetic high entropy alloy ingot was hot rolled at 1000°C with a deformation of 90%, and then naturally cooled in air. The hot-rolled alloy was subjected to high-temperature solution treatment at a temperature of 1200°C for 30 min, and then water-cooled to obtain Fe 34.9 Co 29 Ni 25 Al6Ti5Mo 0.1 High-strength plastic soft magnetic high-entropy alloy.
[0052] Figure 1 The Fe prepared in Example 1 34.9 Co 29 Ni 25 Al6Ti5Mo 0.1 The room temperature tensile engineering stress-strain curve of the high-strength plastic soft magnetic high-entropy alloy shows excellent mechanical properties, with a tensile yield strength of up to 1046MPa, a tensile strength of up to 1230Mpa, and an elongation after fracture of more than 21%. Figure 2 For the preparation of Fe in Example 1 34.9 Co 29 Ni 25 Al6Ti5Mo 0.1 The hysteresis loop and the enlarged view of the central area of the soft magnetic high entropy alloy show that its saturation magnetization (Ms) is 120.8emu / g and its coercive force (Hc) is 1.26Oe, showing excellent soft magnetic properties. Figure 3 The Fe prepared in Example 1 34.9 Co 29 Ni 25 Al6Ti5Mo 0.1 The XRD diffraction analysis spectrum of the high-strength plastic soft magnetic high-entropy alloy shows that the alloy presents a single FCC diffraction peak, with no other diffraction peaks appearing. Figure 4 The Fe prepared in Example 1 34.9 Co 29 Ni 25 Al6Ti5Mo 0.1 The SEM microstructure of the high-strength plastic soft magnetic high-entropy alloy shows a single-phase structure of equiaxed crystals.
[0053] Example 2
[0054] This embodiment discloses a high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy, the general formula of which is Fe 31.8 Co 32 Ni25 Al6Ti5Mo 0.2 .
[0055] In this embodiment, the high-strength and high-plastic Fe 31.8 Co 32 Ni 25 Al6Ti5Mo 0.2 The preparation method of the soft magnetic high entropy alloy is basically the same as that of Example 1, except that the alloy needs to be kept at 750°C for 5 minutes after being kept at 1200°C for 30 minutes.
[0056] Figure 5 The Fe prepared in Example 2 31.8 Co 32 Ni 25 Al6Ti5Mo 0.2 The room temperature tensile curve of the soft magnetic high entropy alloy shows that its room temperature tensile yield strength is 941MPa, the tensile strength is 1127MPa, and the elongation at break is 22%. Figure 6 The hysteresis loop and the local enlarged image of the central area of the high-strength plastic soft magnetic high-entropy alloy prepared in Example 2 have a saturation magnetization intensity (Ms) of 125.23emu / g and a coercive force (Hc) of 1.65Oe. The alloy has excellent mechanical properties and soft magnetic properties. Figure 7 The Fe prepared in Example 2 31.8 Co 32 Ni 25 Al6Ti5Mo 0.2 The XRD diffraction analysis pattern of the high entropy alloy is similar to that of Example 1, and only has the diffraction peak of the FCC phase. Figure 8 The Fe prepared in Example 2 31.8 Co 32 Ni 25 Al6Ti5Mo 0.2 The SEM microstructure of the high-entropy alloy also shows a single-phase equiaxed crystal morphology. Fig. 9 3 is a comparison chart of the tensile yield strength of the soft magnetic high entropy alloys in Examples 1 and 2 and commercial soft magnetic alloys. The commercial soft magnetic alloys in the figure are Fe-3Si alloy (silicon steel), Fe-48Ni alloy (Permalloy) and FeCo-2V alloy from left to right. It can be seen from the figure that the soft magnetic high entropy alloys in Examples 1 and 2 exhibit a yield strength far exceeding that of commercial soft magnetic alloys.
[0057] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy, characterized in that: Its general formula is Fe a Co b Ni c Al d Ti e Mo f , where 25%≤a≤40%, 28%≤b≤45%, 20%≤c≤30%, 3%≤d≤9%, 2%≤e≤8%, 0.1%≤f≤0.5%, and a+b+c+d+e+f=100%, a, b, c, d, e and f are the molar percentages of the corresponding elements respectively.
2. The high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy according to claim 1, characterized in that: General formula Fe a Co b Ni c Al d Ti e Mo f Satisfies: 60%≤a+b≤70%, 6%≤d+e≤15%.
3. A method for preparing the high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy according to claim 1 or 2, characterized in that: The following steps are involved: Step 1, weigh the raw materials according to the molar ratio of each component in the general formula: Fe, Co, Ni, Al, Ti and Mo; Step 2: placing the raw materials into a vacuum arc melting furnace and melting them under argon protection to obtain a Fe-Co-Ni-Al-Ti-Mo high entropy alloy ingot; Step 3: The Fe-Co-Ni-Al-Ti-Mo high entropy alloy ingot is subjected to hot rolling deformation treatment, and the hot-rolled alloy is kept at 1100° C. to 1250° C. for 10 to 30 minutes to prepare a Fe-Co-Ni-Al-Ti-B high-strength plastic soft magnetic high entropy alloy.
4. The method for preparing the high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy according to claim 3, characterized in that: Before smelting the alloy raw materials, the low-melting-point Al needs to be placed at the bottom of the crucible, the high-melting-point Mo and Ti elements need to be placed at the top, and the remaining Fe, Co, and Ni elements need to be placed in the middle.
5. The method for preparing the high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy according to claim 3, characterized in that: Before smelting, the vacuum in the arc furnace smelting chamber should be pumped to 3×10 -3 ~4×10 -3 Pa, and then high-purity argon gas is filled in to -0.05~-0.04MPa.
6. The method for preparing the high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy according to claim 3, characterized in that: Before melting the alloy, the single Ti ingot needs to be melted repeatedly for 3 to 5 times, each time for 1 to 3 minutes.
7. The method for preparing the high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy according to claim 3, characterized in that: The current for melting the alloy is 300-550A, and the melting is repeated 5-8 times, each time for 1-4 minutes.
8. The method for preparing the high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy according to claim 3, characterized in that: The rolling temperature of the hot rolling deformation treatment is 900-1200° C., and the total deformation amount is 60%-90%.
9. The method for preparing the high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy according to claim 3, characterized in that: The Fe-Co-Ni-Al-Ti-Mo high entropy alloy ingot is kept at the rolling temperature for 10-60 minutes, hot rolled and deformed, and then air-cooled. The subsequent heat treatments are all water-cooled.
10. Use of the high-strength and high-plasticity Fe-Co-Ni-Al-Ti-Mo soft magnetic high-entropy alloy according to claim 1 or 2 in the electromagnetic field.
Citation Information
Cited By
Soft magnetic high-entropy alloy with high strength, high plasticity and low coercive force and preparation method thereof
CN121802264A